Pengaruh Kompensasi terhadap Kinerja Perangkat Nagari dalam Pengelolaan Keuangan Nagari di Kecamatan Salimpaung - Rahmi Suci; Syamsir Syamsir (Journal of Education on Social Science (JESS), 2018)
This study revealed the effect of compensation on the performance of nagari apparatus in the management of nagari finance in Kecamatan Salimpaung, Tanah Datar District. This study used associative quantitative method. The population in this study is all nagari apparatus in Kecamatan Salimpaung as many as 42 people consisting of nagari secretary, nagari treasurer, and staffs. The sample of this study consisted of 38 respondents determined by multistage random sampling technique and used slovin formula. The data of this study were collected through questionnaire and analyzed with multiple linear regression analysis technique. The results of this study indicated that compensation simultaneously had a significant effect on the performance of nagari apparatus in the management of nagari finance in Kecamatan Salimpaung. Partially, finansial compensation had a significant influence on the performance of nagari apparatus in nagari finansial management; while non-finansial compensation had no significant effect on the performance of the nagari apparatus in the management of nagari finance in Kecamatan Salimpaung.